Analisis sistem dan prosedur akuntansi pengeluaran kas pada kantor Kecamatan Tikala Kota Manado - Runturambi, Monica Anastasya (Riset Akuntansi dan Portofolio Investasi, 2025)
This study analyzes the accounting system and procedures for cash disbursements at the Tikala Sub-district Office, Manado City, in accordance with Government Regulation No. 12 of 2019 on Regional Financial Management. Motivated by the need for transparency and accountability in public fund management, the study employs a descriptive qualitative approach using interviews, observation, and documentation as data collection methods. The results show that the cash disbursement system at the Tikala Sub-district Office follows a structured sequence involving the issuance of a Budget Provision Letter (SPD), Payment Request Letter (SPP), Payment Order Letter (SPM), Fund Disbursement Order (SP2D), and Accountability Report (SPJ). These stages serve as control mechanisms to ensure compliance with regulations and enhance transparency and accountability in regional financial management. The study concludes that improving the integration of the accounting information system, strengthening internal control, and enhancing human resource capacity are essential steps to optimize the cash disbursement system in local government institutions.